Minat Baca Berita Generasi Y dan Z Melalui Headline Instagram Carousel Liputan6.com - Salsabilla, Safira; Ridho, Kholis; Suhaimi, Suhaimi (Faculty of Da'wa and Communications Sciences, 2023)
There are various personal reasons someone is interested in reading the news. Apart from the level of education, the abundance of information, generational differences, even production strategies and the appearance of news publications shape people's new habits in consuming news. There are those who believe that the appearance of news packaging influences interest in reading news and in other side interest in reading news depends on the substance of the content. This research tests whether there is an influence of the Liputan6.com headline carousel on generation Y and Z's reading interest in news content. Liputan6.com carousel content is posted on its official Instagram account. Carousel content is one of the results of technological developments in the field of journalism in terms of news publications. The carousel platform is relatively new because it was released in 2017 and is still used today. The theory used in this research is SOR proposed by Hovlan, Janis and Kelley. This theory assumes that the stimulation provided by the mass media in the form of news has an effect on the communicant. The research uses a quantitative approach with a questionnaire instrument. The data results were processed using Simple Linear Regression Test statistics to find the influence of the carousel headline and the quality of the carousel content on the reading interest of generations Y and Z, both partially and simultaneously. Based on the research results, it can be concluded that there is an influence from carousel headlines on generation Y and Z's reading interest in Instagram @liputan6 carousel content of 39.4%.